Pemanfaatan Ekstrak Daun Beluntas (Pluchea Indica Less) Dalam Air Minum Terhadap Kualitas Daging Ayam Broiler - Mihrani M; Nurfitri Aqizah; Herlina H (Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine the effectiveness of beluntas leaf extract (Pluchea indica Lesser) on broiler meat quality. The study was conducted at the Poultry Installation of the Gowa Agricultural Development Polytechnic, and meat quality testing was conducted at the Animal Health Laboratory of the Gowa Agricultural Development Polytechnic. A Completely Randomized Design (CRD) was used in this study, with four treatments and four replications, each consisting of four broiler chickens. The beluntas leaf extract was administered twice daily at different doses: 0 ml (P0), 5 ml (P1), 10 ml (P2), and 15 ml (P3). Parameters observed included broiler meat texture, color, odor, and flavor. Data were analyzed using analysis of variance, followed by Duncan's test. The results showed that beluntas leaf extract significantly affected broiler meat quality (P<0.05). Based on the data for each parameter with various treatments, the best treatment is P3, with the administration of 15 ml/l of beluntas leaves.